Mobile-Assisted Language Learning: Exploration of EFL Middle School Students’ Perspectives - Khafifah, Windi Nur; Fithrijah, Siti Salisa; Rakhmawati (ICONELT, 2024)
This study aimed to explore the use of Mobile-Assisted Language Learning (MALL) from students’ perspectives in learning English as a Foreign Language (EFL) among middle school students. This study found patterns of mobile technology use among students, commonly used applications, and obstacles faced when using mobile technology in the learning process. This study also used a mixed-method methodology, which combined questionnaires and semi-structured interviews in the data collection process. The subjects for this study were 18 eighth-grade students from SMPN 1 Lamongan in the 2023/2024 academic year, and they were selected using a random sample. The results of the questionnaire showed that most of them had used mobile devices for over three years. The most common thing found was that they used this tool to help understand vocabulary, especially using Google Translate. Not only that, they also underlined the obstacles they faced when learning using mobile technology, such as difficulty in understanding certain contexts and distractions from non-educational contexts. Although MALL has positive potential as a medium for learning English as a Foreign Language (EFL), more improvements are still needed in application design and instructional approaches to optimize its use. This study is expected to broaden the insight about MALL in English language learning. This study offers a new perspective for educators, application developers, and policymakers who want to utilize mobile technology in the English language teaching process.